Rapid characterisation of grape seed extracts by a novel HPLC method on a diol stationary phase - Stefanie Kuhnert (Journal of Functional Foods, 2015)
Oligomeric proanthocyanidins (OPC) are important dietary supplements due to their well-known health benefits with an average market share of 150 tonnes per year for nutraceuticals. To protect consumers from deceptive declarations related to the OPC-content, an HPLC method using a diol stationary phase column for quantification of OPC was developed. The method allows the quantification of individual classes of dimeric to pentameric proanthocyanidins besides the monomeric flavan-3-ols and polymeric proanthocyanidins for the first time. In this study polymeric procyanidins are referred to a chain length >5 flavan-3-ol units. The method was applied to the analysis of commercial grape seed extracts and the results of the method were compared with spectrophotometric assays. Results obtained by the HPLC method were in the range of 76–99% of total OPC. The spectrophotometric assays provided results from 70 to 110% (acid butanol assay) and 28 to 45% for OPC (vanillin assay). The Folin–Ciocalteu assay yielded amounts for total phenols from 78 to 93%.